Mucormycosis threats: A systemic review. (4th November 2022) - Prakash, Shaurya; Kumar, Antresh
Abstract: During the catastrophic wave of Coronavirus disease 2019, health agencies started to report an infrequent but lethal mucormycosis or black fungal infection. Primarily, it causes sinusitis by affecting nasal, oral, lung, brain, ocular, and other body tissues. It becomes more fatal, especially in diabetic, cancer, and immune‐compromised patients. Before 2020, the prevalence of mucormycosis was very rare but it has rapidly emerged globally from late 2020 to mid‐2021. Recently, the mucormycosis got worse and epidemic with more than 30, 000 cases reported across India. The etiology of infection can be diagnosed by molecular, serological, microscopic, and clinical methods. However, early diagnosis of this ailment is still a challenging task due to no standalone diagnostic tool available along with clinical manifestations of the ailment resembling other fungal diseases. The treatment of mucormycosis is also challenging and frequently requires long‐term treatment. Amphotericin B was found to be an effective antifungal for preventing mucormycosis but it failed if infection disseminated to necrotizing tissues or adjacent organs. Removal of infected tissue/organ by surgery is an alternative treatment to control mucormycosis. In addition, reversal of underlying predisposing conditions based on therapy is also in practice for its prevention. This review highlights different aspects of mucormycosis such as pathogenesis, diagnosis, treatment, and their challenges and so on. We also emphasized the epidemiological shift during the recent outbreak and its influence on the different regions of India.